New water-soluble benzophenone derivatives as initiators of free radical polymerization of acrylates - Ścigalski, F.; Pączkowski, J. (Polimery, 2022)
Triplet state quenching of benzophenone derivatives in the presence of amino-acids undergoes via photoinduced intermolecular electron transfer mechanism (PET), which is followed by the transformations yielding free radicals able to initiate polymerization. This paper describes a series of water soluble free radical photoinitiating systems consisting of sodium 4-benzoylbenzenesulfonate (BBS) and sodium 4,4’-dibenzoylbenzenesulfonate (DBBS) as the light absorbing chromophores and amino acids or sulfur-containing amino acids acting as the electron donors. Photoinitiated polymerization were carried out for the mixture composed of poly(ethylene glycol)diacrylate (PEGDA) - 1 % NH4OH (3:1). The mechanistic aspect of photoinitiating processes was investigated by the measurement of polymerization kinetics and by the nanosecond laser flash photolysis. The photoreduction of benzophenone derivatives in the presence of the electron donors was studied in acetonitryle and water solutions. Nanosecond laser flash photolysis indicated a weak efficiency of ketyl radical formation (lmax = 550 nm), which is due to the hydrogen atom abstraction by the excited triplet state of the sulfobenzophenone chromophore. It is also documented that in the presence of amino acids or sulfur containing amino acids PET process leads to formation of a-aminoradicals that can initiate PEGDA polymerization. Based on photochemistry of tested benzophenone derivatives, photochemistry of sulfur-containing amino acids and obtained results the mechanism describing primary and secondary processes occurring during photoinitiated polymerization via PET process is proposed.